Short-Term Shocks and The Resilience of Islamic Stocks: Evidence From The Dow Jones Islamic Turkey Index - Eşref Devabe (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
This study examines how internal factors exchange rates, interest rates, and inflation and external variables global oil and gold prices, the 2008 financial crisis, and the COVID-19 pandemic affect the performance of Shariah-compliant stocks listed on the Dow Jones Islamic Turkey Index. Although Islamic equity markets are gaining prominence, limited research addresses their response to macroeconomic shocks, particularly in emerging economies. This study aims to fill that gap by evaluating both short-term and long-term effects of selected variables using monthly data from January 2007 to September 2024. The Autoregressive Distributed Lag (ARDL) model is employed to identify cointegration and dynamic relationships. The results indicate a long-run equilibrium among variables but show no significant long-term effects on index performance. In contrast, short-term analysis reveals that exchange rate fluctuations and the COVID-19 pandemic significantly and negatively affect Islamic stock performance, with respective impacts of 48% and up to 14%. The findings suggest that while Islamic stocks demonstrate resilience over time, they remain vulnerable to short-term shocks. This highlights the critical role of exchange rate volatility and pandemic-driven uncertainty in shaping investor confidence. The study contributes to Islamic finance literature by offering empirical insights into how macroeconomic dynamics influence Islamic stock indices and provides practical guidance for investors and policymakers aiming to enhance risk management and develop resilient investment strategies in Shariah-compliant markets.